2008
DOI: 10.1016/j.crte.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Tortonian salinity crisis in the Fortuna Basin (southeastern Spain): Stratigraphic record, tectonic scenario and chronostratigraphy

Abstract: The Neogene Fortuna and Bajo Segura basins are located on the northeastern end of the Trans-Alborán Shear Zone (TASZ), on the eastern Betic cordillera. The stratigraphic study of the infilling of these basins has shown two major sedimentary discontinuities. The first one, represented by an erosive surface separating open marine marls from an overlying coastal conglomeratic unit, is linked to the onset of the activity along the TASZ, which in this area indicates the beginning of the Abanilla Thrust emplacement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
6
0
4
Order By: Relevance
“…Nevertheless, several authors supported on the paleontological record, suggested that this basin shows an early restriction event before the main Messinian Salinity Crisis. That favored a Tortonian Salinity Crisis (7.6-7.8 Ma), proposed as the consequence of a tectonic uplift event isolating the eastern Betic basins (Corbí et al, 2012;Garcés et al, 1998Garcés et al, , 2001Krijgsman et al, 2000;Lancis et al, 2010;Montenat et al, 1987;Tent-Manclús et al, 2008).…”
Section: Tectonicsmentioning
confidence: 99%
“…Nevertheless, several authors supported on the paleontological record, suggested that this basin shows an early restriction event before the main Messinian Salinity Crisis. That favored a Tortonian Salinity Crisis (7.6-7.8 Ma), proposed as the consequence of a tectonic uplift event isolating the eastern Betic basins (Corbí et al, 2012;Garcés et al, 1998Garcés et al, , 2001Krijgsman et al, 2000;Lancis et al, 2010;Montenat et al, 1987;Tent-Manclús et al, 2008).…”
Section: Tectonicsmentioning
confidence: 99%
“…La correlación entre paleofacies (ver Tabla 2) se aborda desde la integración de estas en secuencias de depósito donde el Sintema o ciclo estratigráfico básico se entiende como cuerpo rocoso limitado por discontinuidades significativas a nivel regional (Chang, 1975;Salvador, 1984;Tent Manclús, 2003) Este sistema de correlación es similar al aplicado en registros mediterráneos coetáneos y a priori semejantes (Mioplioceno italiano, Rovieri et al, 2001; Neógeno de la cuenca del Segura, Tent Manclús, 2003;Corbí, 2010;2017;.…”
Section: Materiales Y Métodosunclassified
“…El Messiniense marino mediterráneo presenta dos ciclos sedimentarios principales (Van Assen et al, 2006;Montenat, 1990;Tent Manclús, 2003;Corbí, 2010;2017; La transgresión marina messiniense se expresa en aguas mediterráneas con la entrada de foraminíferos planctónicos como Globorotalia miotumida (Jenkins) o Globorotalia. Mediterránea (Catalano & Sprovieri) (Hilgen et al, 2000;Sierro et al, 1993;Krijgsman et al, 1994;.…”
Section: Interpretación Estratigráficaunclassified
See 2 more Smart Citations